Asymmetric Synthesis of cis-5-(Aminomethyl)-3-(4-methoxyphenyl)dihydrofuran-2(3H)-one - Kim, Sonhwan; Lee, Won Koo; Ha, Hyun-Joon (Synthesis, 2019)
The asymmetric synthesis of (3R,5S)-5-(aminomethyl)-3-(4-methoxyphenyl)dihydrofuran-2(3H)-one, as the most potent selective inactivator of monoamine B, was successfully achieved by applying a newly developed synthetic method toward the key γ-aminomethyl-γ-lactone via intramolecular aziridine ring opening in 63% overall yield from a commercial starting material.
Keywords: asymmetric synthesis; γ-aminomethyl-γ-lactone; aziridines; ring opening